Kinin Peptides Enhance Inflammatory and Oxidative Responses Promoting Apoptosis in a Parkinson’s Disease Cellular Model - Anna Niewiarowska-Sendo; Andrzej Kozik; Ibeth Guevara-Lora (Mediators of Inflammation)
Kinin peptides ubiquitously occur in nervous tissue and participate in inflammatory processes associated with distinct neurological disorders. These substances have also been demonstrated to promote the oxidative stress. On the other hand, the importance of oxidative stress and inflammation has been emphasized in disorders that involve the neurodegenerative processes such as Parkinson’s disease (PD). A growing number of reports have demonstrated the increased expression of kinin receptors in neurodegenerative diseases. In this study, the effect of bradykinin and des-Arg10-kallidin, two representative kinin peptides, was analyzed with respect to inflammatory response and induction of oxidative stress in a PD cellular model, obtained after stimulation of differentiated SK-N-SH cells with a neurotoxin, 1-methyl-4-phenylpyridinium. Kinin peptides caused an increased cytokine release and enhanced production of reactive oxygen species and NO by cells. These changes were accompanied by a loss of cell viability and a greater activation of caspases involved in apoptosis progression. Moreover, the neurotoxin and kinin peptides altered the dopamine receptor 2 expression. Kinin receptor expression was also changed by the neurotoxin. These results suggest a mediatory role of kinin peptides in the development of neurodegeneration and may offer new possibilities for its regulation by using specific antagonists of kinin receptors.